2016
DOI: 10.2460/ajvr.77.5.487
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the role of the cyclooxygenase signaling pathway during inflammation in skin and muscle tissues of ball pythons (Python regius)

Abstract: OBJECTIVE To determine degrees of production of cyclooxygenase (COX)-1 and -2 and other mediators of inflammation in noninflamed and inflamed skin and muscle tissues in ball pythons (Python regius). ANIMALS 6 healthy adult male ball pythons. PROCEDURES Biopsy specimens of noninflamed skin and muscle tissue were collected from anesthetized snakes on day 0. A 2-cm skin and muscle incision was then made 5 cm distal to the biopsy sites with a CO2 laser to induce inflammation. On day 7, biopsy specimens of skin and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 20 publications
2
8
0
Order By: Relevance
“…Four studies investigating COX expression in reptiles were found and the data are summarized in Table 3 . A similar trend was observed in both eastern box turtles and ball python, where significantly higher COX-1 expression was observed in inflamed than non-inflamed tissue, whereas no significant change in COX-2 expression was observed during inflammation ( Royal et al., 2012 ; Sadler et al., 2016 ). However, in the eastern box turtles, COX-2 expression was higher in inflamed than non-inflamed tissue by two-fold although it was not considered significant ( Royal et al., 2012 ).…”
Section: Pharmacodynamic Datasupporting
confidence: 76%
See 2 more Smart Citations
“…Four studies investigating COX expression in reptiles were found and the data are summarized in Table 3 . A similar trend was observed in both eastern box turtles and ball python, where significantly higher COX-1 expression was observed in inflamed than non-inflamed tissue, whereas no significant change in COX-2 expression was observed during inflammation ( Royal et al., 2012 ; Sadler et al., 2016 ). However, in the eastern box turtles, COX-2 expression was higher in inflamed than non-inflamed tissue by two-fold although it was not considered significant ( Royal et al., 2012 ).…”
Section: Pharmacodynamic Datasupporting
confidence: 76%
“… N.R. Reference ( Buch et al., 2018 ) ( Buch et al., 2017 ) ( Royal et al., 2012 ) ( Sadler et al., 2016 ) ( Sadler et al., 2016 ) a Referring to COX expression or activity during inflammation in comparison to normal conditions. b Four suffered from head trauma, while one suffered from maggot infestation which led to amputation N.R., not reported.…”
Section: Pharmacodynamic Datamentioning
confidence: 99%
See 1 more Smart Citation
“…To the authors’ knowledge, the current information about ketorolac in turtles is limited to one published eastern box turtle study, one abstract on eastern box turtles and yellow‐bellied sliders, and two loggerhead case reports (Cerreta et al, 2019; Henson & Lewbart, 1998; Jaeger et al, 2003; Lewbart et al, 2001). As a nonselective cyclooxygenase (COX) inhibitor, ketorolac may provide broader analgesic coverage in reptiles than more selective COX inhibitors such as meloxicam, based on the variable increase in expression of both COX‐1 and COX‐2 receptors following trauma in reptiles (Perry & Nevarez, 2018; Royal et al, 2012; Sadler et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Previous pharmacokinetic studies in loggerhead turtles ( Caretta caretta ) evaluating meloxicam, a COX‐2 selective NSAID, at 0.1 mg/kg IM and IV and 0.2 mg/kg IV, found low plasma concentrations with more rapid elimination than in mammals; therefore, the authors did not recommend meloxicam at those doses for sea turtles (Claus et al., ; Lai et al., ). Studies of COX‐1 and COX‐2 expression in eastern box turtles ( Terrapene carolina carolina ) (Royal, Lascelles, Lewbart, Correa, & Jones, ) and ball pythons ( Python regius ) (Sadler et al., ) suggest the possibility that a nonselective NSAID with both COX‐1 and COX‐2 activity, such as ketoprofen, may be more efficacious in controlling pain and inflammation in chelonians than a COX‐2 selective drug. Ketoprofen also has the advantage in the United States and some other countries of having a commercially available veterinary formulation for injection at a concentration convenient for larger turtles (Ketofen®, 100 mg/ml solution).…”
Section: Introductionmentioning
confidence: 99%